Profile and Antibiotic Assay of Cefotaxime-Resistant Lactic Acid Bacteria from The Caecum of Broiler Chickens - Rosyunita, Rosyunita; Wardoyo, Eustachius Hagni; Rahim, Adelia Riezka; Nurmi , Hasbi (Jurnal Biologi Tropis, 2024)
A health problem associated with increasing antibiotic resistance, the silent pandemic kills 700,000 people a year, mostly in Asia and Africa. In the case of probiotic or lactic acid bacteria, antibiotic resistance can enhance nutrient absorption in the host and prevent the colonization of pathogenic bacteria. To address this, the WHO has suggested using the One Health Tricycle strategy, which entails monitoring people, the environment, and animals. One facet of this investigation is animals, specifically chickens. This study aims to identify the antibiotic resistance and profile of cefotaxime-resistant lactic acid bacteria (LAB) from broiler chicken cecum. Isolating LAB from the chicken's cecum is one of the techniques employed. After calculating the prevalence of resistant bacteria, the bacteria were characterized as macroscopic, microscopic, and biochemically. Testing the antibiotics against LAB was the next stage. According to the study's findings, the bacterial colonies were tiny to medium-sized, white, spherical, and convex, with complete margins. Gram-positive bacilli were identified by Gram staining. The findings of the biochemical tests were negative for oxidative and catalase, positive for glucose, and negative for other biochemical tests. According to antibiotic sensitivity testing, LAB was 90.9% resistant to Vancomycin, 63.63% to Chloramphenicol, and 100% to Erythromycin, Aztreonam, and Ceftriaxone. According to these findings, LAB in the chicken caecum has become resistant to several antibiotics. To give a better picture of the balance between pathogenic and helpful bacteria in the chicken cecum, more LAB testing against pathogenic bacteria is required.